2022
DOI: 10.5860/crl.83.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Personal Librarians on Academic and Affective Outcomes

Abstract: Many academic libraries have implemented personal librarian programs, seeking to improve relationships with students and reduce library anxiety. This pilot study, in which a personal librarian was assigned to sections of a general education course, aimed to expand upon the personal librarianship literature by assessing whether a personal librarian influences student academic outcomes and information literacy confidence. Results from the pilot suggest that the presence of and engagement with the personal librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…By having an assigned librarian, students can be aware that they have someone to introduce them to library resources and research concepts that are appropriate for their STEM coursework, which was found to be correlated with confidence in information literacy. 17 However, it is important to acknowledge 'While all students can experience research anxiety, underserved populations may be more vulnerable to it' 'embedded instruction allowed students to engage with information literacy concepts and competencies directly through a course' that personal librarian programs can be difficult to scale to larger colleges and universities, so this option should only be implemented on a contextual basis. Fundamentally, all of these programs have proven potential to assist students with achieving academic success.…”
Section: Ideas For How Information Literacy Can Be Foundational In Ef...mentioning
confidence: 99%
“…By having an assigned librarian, students can be aware that they have someone to introduce them to library resources and research concepts that are appropriate for their STEM coursework, which was found to be correlated with confidence in information literacy. 17 However, it is important to acknowledge 'While all students can experience research anxiety, underserved populations may be more vulnerable to it' 'embedded instruction allowed students to engage with information literacy concepts and competencies directly through a course' that personal librarian programs can be difficult to scale to larger colleges and universities, so this option should only be implemented on a contextual basis. Fundamentally, all of these programs have proven potential to assist students with achieving academic success.…”
Section: Ideas For How Information Literacy Can Be Foundational In Ef...mentioning
confidence: 99%